Subjective evaluation of ﬂoor impact noise using the tapping machine and a non-standardized source - Panosso, Andriele da Silva (2022)
Assessing the acoustical performance of building floor systems relies on the impact source to be utilized and on the type of floor cover used. Besides that, a reliable assessment should consider the listeners’ judgments of the sounds transmitted through floors or radiated by them. Objective ratings measured can help to foresee tenant satisfaction provided that they are well correlated with the listeners’ judgments. The main objective of this study was to compare objective and subjective evaluations, using two types of impact sources and two types of floor covers, to try and determine which objective variables could be used to predict subject evaluation and to validate the use of an alternative impact source to be used in more realistic measurements. An objective evaluation was carried out employing impact noise insulation measurements according to ISO 10140:2010, evaluating different types of floors, resilient materials, and impact sound sources (a standardized tapping machine and a calibrated tire). In the analysis of the measured samples, several parameters were evaluated according to the sound source used. Simultaneously, "sound samples" were recorded to be used in a subjective evaluation based on the judgments of 29 listeners about the Noise Annoyance and the Loudness Sensation in response to the two impact sources. The magnitude estimation method was used. Results demonstrate that tapping machine measurements correlate very well with the subjective evaluation measurements and the calibrated tire presents well-correlated results in a specific measurement set-up. In addition, linear regression analysis of the objective and subjective variables shows alternative single number quantities for ratings of impact noise insulation